VD_FINDINFO Décision / 2014 / 539 vom 23. Juni 2014 - VD Tribunal cantonal (2014)
DÉTENTION PROVISOIRE, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)